TRANSLATION FEATURES OF RICHARD RUSSO'S NOVEL "EMPIRE FALLS" - Liana Vartanova (Гуманитарные и юридические исследования)
The article is devoted to genre and style features analyses of the modern American novel, which peculiarity is based on the author's, not typical for fiction description of the reality, with the unique manipulative influence on the reader that proves the intellectual originality of the given text. This characteristic feature is reflected in the main character speeches, which make them realize the life purpose, make a choice, gain faith and be ready to contradict the illusion and the reality. Grammar peculiarity of the text is the usage if simple and expanded sentences. The necessity to distinguish the information bit, to understand and comprehend it, is the main pragmatic feature of the text. Translation of the action requires preservation of esthetic and pragmatic influence on the reader and preconditions the use of translation transformations at different levels. Besides, it is important to consider the basic knowledge of the representatives of different linguocultures, which may lead to an inadequate comprehension of the original text. The grand purpose of the text translation is to preserve the emotional tense of the main character's relations, which is presented with the help of different means of artistic emphasis. Translator factor plays the key role due to the twofold position of the latter, namely the recipient of the original text and the source of the translation.